2011
DOI: 10.4028/www.scientific.net/amm.117-119.332
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Derived Titania/Hydroxyapatite Layer on Titanium Substrate

Abstract: In this study, calcium nitrate(Ca(NO3)2•4H2O) and phosphorus pentoxide(P2O5) were used as precursor to prepare hydroxyapatite(HA) layer by sol-gel method, followed by a dipping-coating method to coat HA layer onto Ti. Phase formation and microstructure were investigated by XRD and SEM to study the influence of atmosphere on the property of HA layer. The results revealed that there exists no large cracks in the layer which was heated in the nitrogen, leading to a good surface quality compared with the layer whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The cross-sectional images ( Figure 4 E,F) showed the coatings had a homogeneous thickness of approximately 7 μm. In fact, the coating thickness could be easily adjusted by controlling the deposition times during the dip-withdrawal process [ 25 ]. The cross-sectional view also confirmed that the coating was densely compacted without visible micro-cracks.…”
Section: Resultsmentioning
confidence: 99%
“…The cross-sectional images ( Figure 4 E,F) showed the coatings had a homogeneous thickness of approximately 7 μm. In fact, the coating thickness could be easily adjusted by controlling the deposition times during the dip-withdrawal process [ 25 ]. The cross-sectional view also confirmed that the coating was densely compacted without visible micro-cracks.…”
Section: Resultsmentioning
confidence: 99%